DIPHTHERIA TOXIN PRODUCTION IN PILOT SCALE USING CASEIN BASED MEDIA - PREETHI S.; BHEEMAN SUNDARAN; BALARAMAN SEKAR (International Journal of Pharma and Bio Sciences, 2018)
In diphtheria vaccine production, a high level purity of the antigen is imperative. Corynebacterium diphtheriae is an exotoxin producing infectious bacteria. It is cultivated in a media which supports its growth. For decades the media used was meat based in nature. Presently with WHO CDS guidelines, and also due to presence of undesirable protein presence, the use of meat based media is at disputation leading to a few countries opting to avoid meat. Thus a need for an alternative media has arisen. In the present study a complete meat free, a milk protein-casein based media was used. The adaptability of the bacteria in the media, its growth and toxin release was studied using cultural and toxin analysis parameters such as amino nitrogen estimation, Optical density and Limes flocculation (Lf titre), Protein estimation respectively. In this study it was observed that the media supports the growth with a steady increase in the optical density denoting growth and Lf of 30-50 units with a short flocculation time denoted as Kf in a shaking culture method. The produced toxin has a significant antigenic purity.